The components of physical fitness, its relationship to health status in universities students/Los componentes de la condición física, su relación con el estado de salud en estudiantes universitarios - Jesús Costa Acosta; Manuel Rafael Valdés López Portilla; Alexis Rodríguez Madera; Annette Núñez González (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
This article aims to internalize the importance and benefits of the regular practice of physical activity. The objective of this work consisted in carrying out a study of the components of health-related physical fitness in students of the Bachelor's Degree in Socio-Cultural Studies of the University of Pinar del Río "Hermanos Saíz Montes de Oca". Nineteen first year students of this career were randomly selected. Theoretical and empirical research methods were used, such as document analysis and measurement. The values obtained, in terms of the percentage of fat, indicate that the risk factor of excessive fat accumulation can lead to the appearance of several chronic non-communicable diseases. In addition, it is evident that 73% of the investigated sample presents deficiencies in the maximum aerobic power, that is, to supply the necessary oxygen to the muscles during a maximum physical effort. In general, the sample reaches an acceptable level that allows them to maintain an effort at medium or low intensity with sufficient oxygen supply. Therefore, it is necessary to strictly comply with a plan of actions aimed at modifying the body composition of the students under study.